Discontinuation of Semaglutide Therapy for Obesity Management - Aurélie Mailhac; Lars Pedersen; Irene Petersen; Anton Pottegård; Henrik T. Sørensen; Reimar W. Thomsen (JAMA Network Open, 2026)
This cohort study examines the risk of and baseline variables associated with discontinuation of semaglutide treatment for obesity management among individuals in Denmark.